A Simple and Rapid Procedure for the Detection of Genes Encoding Shiga Toxins and Other Specific DNA Sequences - Nejman-Faleńczyk, Bożena (Toxins (Basel), 2015)
A novel procedure for the detection of specific DNA sequences has been developed. This procedure is based on the already known method employing PCR with appropriate primers and a sequence-specific DNA probe labeled with the fluorescent agent 6-carboxylfluorescein (FAM) at the 5′ end and the fluorescence quencher BHQ-1 (black hole quencher) at the 3′ end. However, instead of the detection of the fluorescence signal with the use of real-time PCR cyclers, fluorescence/luminescence spectrometers or fluorescence polarization readers, as in all previously-reported procedures, we propose visual observation of the fluorescence under UV light directly in the reaction tube. An example for the specific detection of the Shiga toxin-producing Escherichia coli (STEC) strains, by detecting Shiga toxin genes, is demonstrated. This method appears to be specific, simple, rapid and cost effective. It may be suitable for use in research laboratories, as well as in diagnostic units of medical institutions, even those equipped only with a thermocycler and a UV transilluminator, particularly if rapid identification of a pathogen is required.